(untitled) (Journal of Preventive and Social Medicine, 2026)
Background: Pesticide toxicity is a major concern in Bangladesh, where agriculture is the backbone of the economy. Horticulture, a rapidly growing subsector, exposes workers to pesticides, making knowledge of usage and toxicity symptoms crucial. Pesticides adversely affect human health, animals, and the environment. The increasing demand for food production has led to greater pesticide use, raising concerns about exposure and adverse effects. Methods: This was a cross-sectional study which was conducted on the population of 236 rural horticulture workers of Munshiganj district, Dhaka, Bangladesh from January to December 2021. The study place was selected purposively and respondents were selected conveniently. Data collection was done by face to face interview with semi-structured questionnaire. Results: Among the 236 respondents, 56.8% were aged >45 years, 89% were male, all were Muslim, and 40.7% had primary-level education. Most (87.3%) were married, 34.3% earned ≤15,000 BDT, and horticulture was their primary income source. About 42.4% had lived in their current residence for 41–60 years, 39.4% had used pesticides for 10–20 years, and 71.2% had not received training from government institutions. Knowledge, assessed using Bloom’s cut-off, revealed 61% had moderate, 6.8% had low, and 32.2% had good knowledge. Self-reported toxicity symptoms malaise 89.4%, skin itching 84.7%, headache 83.1%, skin rash 74.2%, epigastric discomfort 62.7% and Abdominal pain 54.7% subsequently. Significant associations (p<0.05) were found between age, gender, marital status, pesticide use duration, and government training with some symptoms. Conclusion: The study highlights workers’ knowledge levels and common toxicity symptoms, emphasizing the need for better pesticide-use education and safety measures. Findings can inform policies to enhance safe pesticide practices and reduce toxicity, supporting sustainable horticulture development. JOPSOM 2025; 44(1): 31-36